A metamodel-based Monte Carlo simulation approach for responsive production planning of manufacturing systems. (January 2016) - Li, Minqi; Yang, Feng; Uzsoy, Reha; Xu, Jie
Abstract : Highlights: A metamodel is extended to capture the input–output dynamics for stochastic manufacturing systems. A metamodel-based Monte Carlo simulation (MCS) method is developed. The MCS method is able to quickly simulate a system's output processes with high fidelity. The MCS is embedded in a multi-objective optimization framework for production planning. Abstract: Production planning is concerned with finding a release plan of jobs into a manufacturing system so that its actual outputs over time match the customer demand with the least cost. For a given release plan, the system outputs, work in process inventory (WIP) levels and job completions, are non-stationary bivariate time series that interact with time series representing customer demand, resulting in the fulfillment/non-fulfillment of demand and the holding cost of both WIP and finished-goods inventory. The relationship between a release plan and its resulting performance metrics (typically, mean/variance of the total cost and the fill rate) has proven difficult to quantify. This work develops a metamodel-based Monte Carlo simulation (MCS) method to accurately capture the dynamic, stochastic behavior of a manufacturing system, and to allow real-time evaluation of a release plan's performance metrics. This evaluation capability is then embedded in a multi-objective optimization framework to search for near-optimal release plans. The proposed method has been applied to a scaled-down semiconductor fabrication system to demonstrate the quality of the metamodel-based MCS evaluation and the results of plan optimization.